Pola Pengasuhan Anak Dalam Keluarga Minangkabau (Studi Kasus 5 Keluarga di Nagari Paninjauan, Kecamatan X Koto, Kabupaten Tanah Datar) - Rindu Pilyta; Sri Setiawati; Syahrizal (PT. Hasba Edukasi Mandiri, 2025)
Childcare in Minangkabau is the responsibility of all elements of the family and the environment around the child, but in its development this parenting pattern has undergone various changes due to the times and these changes were then followed by a decrease in the role of the extended family in Minangkabau households. This research aims to examine parenting patterns in Minangkabau families, especially in Nagari Paninjauan. This research uses a descriptive qualitative method, using data collection techniques in the form of observation, interviews, literature studies, and documentation. Through case studies of five families, this research found that local culture-based parenting is still applied in daily practice. Nevertheless, each family shows adaptation to the times, integrating modern values without eliminating Minangkabau traditions. This study found that despite social changes, cultural values still function as guidelines in parenting in Minangkabau society. There are also some obstacles experienced due to the development of increasingly modern times